Elastase inhibitor. Characterization of the human elastase inhibitor molecule associated with monocytes, macrophages, and neutrophils (The Rockefeller University Press, 1989)
A fast-acting inhibitor of serine elastase has been detected at high levels in human neutrophils, fresh monocytes, matured monocytes, and macrophages. The elastase inhibitor was isolated from large scale cultures of the monocyte-like cell line U937 by DNase chromatography, disulfide exchange, Phenyl-Sepharose, Red A-agarose, and DEAE HPLC chromatography with an average yield of 480 micrograms from 1.8 x 10(10) cells. The isolated polypeptide was verified as elastase inhibitor by its ability to (a) form a covalent complex with elastase; and (b) inhibit the elastinolytic activity of elastase. The purified elastase inhibitor molecule is unique, i.e., physiochemical and/or functional properties distinguish it from all other serine proteinase inhibitors. Treatment with iodoacetamide abrogates the ability of the molecule to form a complex with elastase, thereby providing evidence for the presence of an essential cysteine residue. Based on functional criteria, this elastase inhibitor has been grouped with the proteinase inhibitors of the serpin superfamily. The purified elastase inhibitor is a single polypeptide of Mr approximately 42,000. The NH2 terminus appears to be blocked. Compositional analyses indicates five cysteine residues per molecule of approximately 360 amino acid residues. Negligible levels of carbohydrate were detected on gas-liquid chromatography. This finding and the insensitivity of the molecule to peptide N-glycosidase F treatment strongly indicate that the elastase inhibitor is a nonglycosylated protein.